A microporous Cu2+ MOF based on a pyridyl isophthalic acid Schiff base ligand with high CO2 uptake12. Issue 12 (13th October 2016) - Kourtellaris, Andreas; Moushi, Eleni E.; Spanopoulos, Ioannis; Tampaxis, Christos; Charalambopoulou, Georgia; Steriotis, Theodore A.; Papaefstathiou, Giannis S.; Trikalitis, Pantelis N.; Tasiopoulos, Anastasios J.
Abstract : A new microporous Cu 2+ MOF is reported containing a pyridyl-isophthalic acid Schiff base ligand which exhibits a significant BET area and high CO2 sorptbion capacity. Abstract : A new Cu 2+ complex that was isolated from the initial use of 5-((pyridin-4-ylmethylene)amino)isophthalic acid (PEIPH2 ) in 3d metal–organic framework (MOF) chemistry is reported. Complex [Cu3 (PEIP)2 (5-NH2 -mBDC)(DMF)]·7DMF∞ denoted asCu-PEIP ·7DMF was isolated from the reaction of Cu(NO3 )2 ·2.5H2 O with PEIPH2 in N, N -dimethylformamide (DMF) at 100 °C and contains both the PEIP 2− ligand and its 5-NH2 -mBDC 2− fragment. After the structure and properties ofCu-PEIP were known an analogous complex was prepared by a rational synthetic method that involved the reaction of Cu(NO3 )2 ·2.5H2 O, 5-((pyridin-4-ylmethyl)amino)isophthalic acid (PIPH2 – the reduced analogue of PEIPH2 ) and 5-NH2 -mBDCH2 in DMF at 100 °C.Cu-PEIP comprises two paddle-wheel [Cu2 (COO)4 ] units and exhibits a 3D-framework with a unique trinodal underlying network and point symbol (4.5 2 )4 (4 2 ·5 4 ·6 4 ·8 3 ·9 2 )2 (5 2 ·8 4 ). This network consists of pillaredkgm-a layers containing a hexagonal shaped cavity with a relatively large diameter of ∼8–9 Å surrounded by six trigonal shaped ones with a smaller diameter of ∼4–5 Å and thus resembles the structure of HKUST-1. Gas sorption studies revealed thatCu-PEIP exhibits a 1785 m 2 g −1 BET area as well as high CO2 sorption capacity (4.75 mmol g −1 at 273 K) and CO2 /CH4 selectivity (8.5 at zero coverage and 273 K).